Chiral self-sorting of giant cubic [8+12] Salicylimine cage compounds - Wagner, Philippe; Rominger, Frank; Zhang, Wen-Shan; Gross, Jürgen H.; Elbert, Sven; Schröder, Rasmus R.; Mastalerz, Michael (Angewandte Chemie, 2021)
Chiral self-sorting is intricately connected to the complicated chiral processes observed in nature and no artificial systems of comparably complexity have been generated by chemists. However, only a few examples of purely organic molecules have been reported so far, where the self-sorting process could be controlled. Herein, we describe the chiral self-sorting of large cubic [8+12] salicylimine cage compounds based on a chiral TBTQ precursor. Out of 23 possible cage isomers only the enantiopure and a meso cage were observed to be formed, which have been unambiguously characterized by single crystal X-ray diffraction. Furthermore, by careful choice of solvent the formation of meso cage could be controlled. With internal diameters of din=3.3-3.5 nm these cages are among the largest organic cage compounds characterized and show very high specific surface areas up to approx. 1500 m2 g−1 after desolvation.